2020
DOI: 10.26434/chemrxiv.12148524.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How ATP-Competitive Inhibitors Allosterically Modulate Tyrosine Kinases That Contain a Src-like Regulatory Architecture

Abstract: <p>Small molecule kinase inhibitors that stabilize distinct ATP-binding site conformations can differentially modulate the glob-al conformation of Src-family kinases (SFKs). However, it is unclear which specific ATP-binding site contacts are responsible for modulating the global conformation of SFKs and whether these inhibitor-mediated allosteric effects are general to other tyrosine kinases. Here, we describe the development of chemical probes that allow us to deconvolute which features in the ATP-bindi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…For the SRC family, the αC-in configuration has been correlated with release of the regulatory domains from the autoinhibited state ( Leonard et al, 2014 ; Tsutsui et al, 2016 ). Other studies suggest that the αC-helix conformation alone can be used to predict the regulatory domain conformation in the SRC, ABL, and TEC kinases; inhibitors that stabilize the αC-in conformation disrupt the regulatory domains from their autoinhibitory conformation, whereas αC-out stabilizing inhibitors do not ( Fang, 2020 ). However, ABL focused studies show that Dasatinib stabilizes αC-in but does not disrupt the regulatory domains from their compact, autoinhibitory state ( Sonti et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the SRC family, the αC-in configuration has been correlated with release of the regulatory domains from the autoinhibited state ( Leonard et al, 2014 ; Tsutsui et al, 2016 ). Other studies suggest that the αC-helix conformation alone can be used to predict the regulatory domain conformation in the SRC, ABL, and TEC kinases; inhibitors that stabilize the αC-in conformation disrupt the regulatory domains from their autoinhibitory conformation, whereas αC-out stabilizing inhibitors do not ( Fang, 2020 ). However, ABL focused studies show that Dasatinib stabilizes αC-in but does not disrupt the regulatory domains from their compact, autoinhibitory state ( Sonti et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We next used the rate of proteolysis of the flexible linker that connects Src’s SH2 domain to its CD (SH2-CD linker) by the metalloprotease thermolysin to characterize how β1/β2 resistance cluster mutations affect intramolecular regulatory domain engagement. Previous studies have demonstrated an inverse correlation between the rate of thermolysin cleavage, measured as intact protein half-life (t1/2), of the SH2-CD linker and intramolecular SH2 and SH3 regulatory domain engagement levels ( Figure 4H ) (Agius et al, 2019; Fang et al, 2020). Concordant with the SH3 domain pull-down results, the SH2-CD linkers of E283M and W285T Src 3D were proteolyzed ∼3 times more rapidly than WT Src 3D ( Figure 4I , S4F ).…”
Section: Resultsmentioning
confidence: 91%
“…Inhibitors 1 , 2 , and 3 was synthesized as previously described in (Ahler et al, 2019; Fang et al, 2020).…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, umbrella sampling computations indicate that the configuration of the SH2 and SH3 regulatory domains, greatly affects the ability of the catalytic domain to adopt the active or inactive conformation [87]. Conversely, individual inhibitors binding to the catalytic domain can have differing allosteric effects on whether the regulatory domains adopt a closed or open conformation [120]. Computational methods based on simplified CG models have played a useful role to interpret SAXS data on Hck kinase in solution in terms of the configuration of the multi-domain kinase [92,101].…”
Section: Relating Computational Studies To Functional Assaysmentioning
confidence: 99%